Copyright, media and modernization in China: A historical review, 1890-2015. - Ren, Xiang (2016)
This article understands the history of copyright and media in China as co-evolution between two conflicting paradigms. One builds on the Confucian and Communist systems, where cultural production and knowledge creation are collective and commons-based, while the other is similar to the western copyright practices characterized by the legal protection and commercial exploitation of proprietary ownership rights of creative works. The article reviews the complex interplay between the two opposed paradigms in different historical periods and explores the tension between the ‘western’ models and the ‘Chinese’ traditions and characteristics in the modernization of copyright and media.